Quantitative decision making - Forgionne, Guisseppi A. (Belmont, California : Wadsworth Publising Inc., 1986)
This book gives an introductory survey of management science/operations research. The text provides complete coverage of today's major quantitative models and show how they are applied to managerial problems in public and private organizations.
Includes index.
ijb 03/09/2018
Loans
Keywords: Management science